Analysis of Denotation and Connotation Meanings in the Song Lyrics "XXL" by LANY - Adira Maesya Sabila; Agus Salim Mansyur; R. Myrna Nur Sakinah (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2026)
Song lyrics function as linguistic signs that convey both literal and implied meanings through symbolic expressions. Although previous studies have applied Roland Barthes’ semiotic theory to analyze song lyrics, limited attention has been given to how ordinary lexical items and everyday expressions function as emotional symbols in contemporary pop music. This study aims to identify the denotative and connotative meanings in the lyrics of “XXL” by LANY and to examine how ordinary expressions are transformed into symbolic representations of intimacy, nostalgia, and emotional attachment through Barthes’ second-order signification. This study employed a qualitative descriptive design. The data source consisted of the official lyrics of “XXL” by LANY. The entire lyrics were examined, while five representative lyric lines were purposively selected for detailed analysis. The data were analyzed using Barthes’ concepts of first-order and second-order signification. The findings reveal that expressions such as small-town dreams, hoodie, Miss Americana, California, and double-XL possess both denotative and connotative meanings. Through second-order signification, these ordinary lexical items function as symbolic signs representing shared aspirations, intimacy, admiration, nostalgia, and enduring emotional attachment. These findings demonstrate that contemporary pop lyrics communicate emotional experiences not only through literal meanings but also through symbolic associations. The study contributes to semiotic studies by providing a deeper understanding of emotional signification in contemporary pop song lyrics through Barthes’ semiotic framework.